Microvillar channels: a unique plasma membrane compartment for concentrating lipoproteins on the surface of rat adrenal cortical cells. - E Reaven; M Spicher; S Azhar (Journal of Lipid Research, 1989)
Electron microscopic studies of perfused rat adrenals indicate that plasma lipoproteins become concentrated in a specialized cell surface compartment called microvillar channels. Closely associated plasma membranes of sinusoidal microvilli of zona fasciculata cells form channels that normally are filled with electron dense particles the size of high density lipoproteins (HDL). In rats made acutely deficient in plasma lipoproteins (by treatment with 4-aminopyrazolo[3,4-d]pyrimidine (4-APP) for 1 day), particles within the microvillar channels are decreased in number. When adrenal glands of these rats are perfused with media lacking plasma lipoproteins, many but not all of these HDL-like particles are washed out. However, when these adrenals are perfused with large amounts (100-500 micrograms protein/ml) of HDL, microvillar channels become packed with electron dense particles similar to those found in vivo. These microvillar channels become wider and filled with larger particles when low density lipoproteins (LDL) are perfused through the adrenals. Autoradiograms of 125I-labeled HDL-perfused adrenals show silver grains specifically associated with the cell surface microvillar channels, and confirm the notion that the particles filling the channels are exogenously delivered HDL. Physiologic data from similarly perfused adrenals in a parallel study show that the channel-refilling process is directly related to selective (i.e., nonendocytic) cholesterol uptake and that this cholesterol uptake is associated with corticosterone production. Together, these data suggest the hypothesis that plasma lipoprotein cholesterol utilized for corticosteroid synthesis in rat adrenal fasciculata cells may be derived from lipoproteins trapped in surface-associated microvillar channels. Although the mechanism responsible for the cholesterol transfer is not yet defined, it is clearly distinct from the classical process of receptor-mediated endocytosis and catabolism of lipoprotein particles.